Supplementary Figure S1 from Randomized Phase II Cabazitaxel Dose Individualization and Neutropenia Prevention Trial in Patients with Metastatic Castration-Resistant Prostate Cancer - Aurelius Omlin (14971513) (2025)
CONSORT Diagram